Minority Group Threat and Racial Profiling: An Analysis of Pretextual Traffic Stops and Outcomes in Missouri Municipalities - Witherspoon, Pernell (2010)
Racial profiling remains a controversial societal issue due in part to difficulties in determining its prevalence. Some analysts have proposed that criminological theories should be used to explain racial profiling. Using the minority group threat hypothesis, this dissertation analyzes the effects of Black population increases on race-based pretextual stops in 113 Missouri municipalities with sizable Black populations. The research also analyzes the effects of the growth and size of the Black population on traffic stop outcomes, including searches, contraband found, arrests, and citations. Other variables that might explain pretextual stops and traffic stop outcomes, including violent crime rates and socioeconomic differences between the Black and White populations, are assessed. The study finds support for the minority group threat hypothesis in explaining racial profiling based on the relative growth and size of the Black population. The hypothesis is refined by results showing the thresholds in the relative size of the Black population at which racially disparate stop rates and outcomes emerge and recede. Community accountability theory also helps to explain the effects of municipal government structure on race differences in traffic stops and outcomes. Although policies that affect population growth would be questionable, policy makers and police organizations should make genuine efforts to reduce profiling by scrutinizing pretextual stops more closely, revising racial profiling forms to reflect more explicit police activity, taking away the ability for officers to make easy outstanding warrant and traffic violation arrests, and requiring documentation of departmental responses to disproportionate stop rates to accompany yearly racial profiling reports to the Attorney General